A Repertory of Rearrangements and the Loss of an Inverted Repeat Region in Passiflora Chloroplast Genomes. (28th July 2020) - Cauz-Santos, Luiz Augusto; da Costa, Zirlane Portugal; Callot, Caroline; Cauet, Stéphane; Zucchi, Maria Imaculada; Bergès, Hélène; van den Berg, Cássio; Vieira, Maria Lucia Carneiro
Abstract: Chloroplast genomes (cpDNA) in angiosperms are usually highly conserved. Although rearrangements have been observed in some lineages, such as Passiflora, the mechanisms that lead to rearrangements are still poorly elucidated. In the present study, we obtained 20 new chloroplast genomes (18 species from the genus Passiflora, and Dilkea retusa and Mitostemma brevifilis from the family Passifloraceae) in order to investigate cpDNA evolutionary history in this group. Passiflora cpDNAs vary in size considerably, with ∼50 kb between shortest and longest. Large inverted repeat (IR) expansions were identified, and at the extreme opposite, the loss of an IR was detected for the first time in Passiflora, a rare event in angiosperms. The loss of an IR region was detected in Passiflora capsularis and Passiflora costaricensis, a species in which occasional biparental chloroplast inheritance has previously been reported. A repertory of rearrangements such as inversions and gene losses were detected, making Passiflora one of the few groups with complex chloroplast genome evolution. We also performed a phylogenomic study based on all the available cp genomes and our analysis implies that there is a need to reconsider the taxonomic classifications of some species in the group.